Liquid medium culture of Quercus suber L somatic embryos comparation between liquid and solid culture and among different growing media - Garcia, G.; Fernandez-Galiano, E.; Mauri, P. V. (HORTICULTURAL BIOTECHNOLOGY IN VITRO CULTURE AND BREEDING, 1997)
The objective of this study was to overcome two of the limiting factors of the standard culture protocol, in agar solidified medium, of cork oak somatic embryos: the low rate of mature embryos obtained, and the high labor and time consumed. First experiment. Immature somatic embryos of 2 mm. length were cultured for 30 days in four different growing media: 1/2SH{*}, SH{*}, 2xSH{*} and MS, both in solid and liquid phase. Higher fresh weights were detected, in every media, using liquid culture. In relation to developmental pattern, liquid culture in 1/2SH{*} has demonstrated to be the most effective combination for the first developmental stages producing lower percentages of secondary embryogenesis. Second experiment. Immature somatic embryos were cultured for 15 days in liquid 1/2SH{*} and transferred to the four different media. The richest media were shown to be more appropriated for the maturation stage giving higher rates of mature embryos.
The following values have no corresponding Zotero field: periodical: HORTICULTURAL BIOTECHNOLOGY IN VITRO CULTURE AND BREEDING issue: 447 pub-location: PO BOX 500, 3001 LEUVEN 1, BELGIUM
Keywords: Cork oak; liquid culture; mature embryos

Multiplicación vegetativa de alcornoque mediante embriogénesis somática. - Garcia-Martin, G.; Fernandez-Galiano, E.; Mauri, P. V.; Somática, Embriogénesis (II Congreso Forestal Español, 1997)
In order to obtain cork oak clones from selected individuals, somatic embryogenesis was induced in leaves. Somatic embryos can be continuously subcultured with high proliferation rates. This culture system has sorne limiting factors: low percentage of mature embryos obtained, low rate of shoot emergence during germination and high labour and time consumed. Exogenous addition of ABA (l0-6M) concentration during proliferation increased maturation rateo In the same way addition of. BAP (0,001 mg/l) had a positive effect on shoot production. With the aim to obtain a first approach to automation the best culture media for both culture cycles of maturation in liquid medium were determined.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: ABA; BaP; Cork oak; germination; liquid culture; maturation; somatic embryos